Anthroponymy of Alans in Official “History of Yuan” - E. V. Kaziev (Научный диалог, 2025)
This article explores the interpretations of the transcriptions of Alan names found in the “History of Yuan.” The aim of the study is to critically analyze the etymological reconstructions of this Alan anthroponymy as presented in scholarly tradition, as well as to generalize and systematize these findings. The phonological system of the Chinese language differs significantly from those of other languages, which hinders the full application of comparative linguistic methods for analyzing much of the onomasticon under consideration. However, diverse sources containing information about ancient, medieval, and modern onomastics, alongside the “History of Yuan,” provided material for this research, allowing for etymological reconstructions and comparisons for most of the analyzed anthroponymic transcriptions. As a result, it was established that 23 out of 38 presented reconstructions are linked to the Alan cultural tradition. The overarching conclusion drawn is that the Alans, who remained at the Mongolian and Yuan courts for one hundred thirty years, preserved their ethnic identity, part of which included their adherence to Christianity. Furthermore, it is noted that the presence of Turkic, Mongolian, and possibly Chinese names in their onomasticon indicates the beginning of Alan assimilation and the influence of Chinese culture on their worldview.